Stability for impulsive control systems - Pereira, F. L.; Silva, Geraldo Nunes [UNESP] (Taylor & Francis Ltd, 2002)
In this paper we extend the notion of the control Lyapounov pair of functions and derive a stability theory for impulsive control systems. The control system is a measure driven differential inclusion that is partly absolutely continuous and partly singular. Some examples illustrating the features of Lyapounov stability are provided.